On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae) - Sankaran, Pradeep M.; Malamel, Jobi J.; Sebastian, Pothalil A. (Zootaxa, 2017)
A new monotypic wolf spider genus, Ovia gen. nov. is proposed to accommodate a misplaced species: Pardosa procurva Yu & Song, 1988. Ovia procurva comb. nov. is redescribed, illustrated and designated as the type species for the genus. The subfamily placement of the new genus is discussed and it is considered as a member of Lycosinae Sundevall, 1833 and possibly closely related to Alopecosa Simon, 1885. The presence of an apical process (spur) on the median apophysis is proposed as the putative synapomorphy of Ovia gen. nov. The possible sister-taxon relationship of Ovia gen. nov. with Alopecosa is discussed and evidence on the occurrence of sexual dimorphism and mating plug within the genus are presented. Ovia gen. nov. is assumed to be of Holarctic origin, from which it has migrated to the Indomalayan region. Additionally, a current distribution map for the genus is provided.